Emerging strategies for the treatment of gastroparesis. (2nd July 2016) - Langworthy, James; Parkman, Henry P; Schey, Ron
ABSTRACT: Gastroparesis is a syndrome of delayed gastric emptying in the absence of mechanical obstruction. Symptoms can be debilitating, affect nutritional states, and significantly impact patients' quality of life. The management of these patients can prove quite difficult to many providers. This article will review the current management recommendations of gastroparesis, discuss investigational medications and interventions, and summarize future directions of therapies targeting the underlying disease process. Current therapies are subdivided into those improving gastric motility and those directly targeting symptoms. Non-pharmacologic interventions, including gastric stimulator implantation and intra-pyloric botulinum toxic injection are reviewed. A discussion of expert opinion in the field, a look into the future of gastroparesis management, and a key point summary conclude the article.